Proximate composition and GC-MS analysis of ethanol extract of Solanum spirale Roxb. - Payum, Temin (Current Botany, 2020)
Solanum spirale Roxb. is abundantly grown in eastern Himalayan regions. The shoot is used as a vegetable as well as medicine to control high blood pressure. The present study was carried out to profile the phytochemical compositions, mineral contents and proximate composition of the Solanum spirale shoot. GC-MS was used for the identification of phytochemicals and methods described in standard protocols were used to study minerals and proximate composition. A total of 40 phytochemicals were recorded from the ethanol extract. Mineral contents of the sample 0.115 (Fe), 0.07 (Mn), 0.015 (Cu), 0.040 (Zn), 2.25 (Mg), 3.08 (Na) and 16.7 (K) mg/g while proximate composition were 76.25± 0.093 % (moisture)3.82±0.26 % (Carbohydrate), 12.54±0.08% (Total ash), 0.39±0.98% (Crude protein), 6.12±1.07 % (Crude fibre), 0.37±0.07 % (Crude fat). (Z,Z)-6,9-Cis-3,4-epoxy-nonadecadiene occupied highest area percentage in TIC peak report with 24.55%, followed by Pentadecanoic acid with 18.81 percent, with Pentadecane with 9.99%, Hexadecanoicacid, Ethyl ester with 8.64%, (2E)(7R,11R)-3,7,11,15-Tetramethylhexadec-2-en-1-ol with 7.75%. Useful phytocompounds related to health problems including anticancer, anti-inflammatory, antioxidant, antitumor, cardioprotective, hypocholesterolemic, increase zinc bioavailability, inhibit uric acid formation, antibacterial, anti-inflamatory, antioxidant etc. are major components and such findings advocate Solanum spirale as a nutraceutical herb.